2019
DOI: 10.1007/978-3-030-30859-9_50
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate Approximation of Resource Request Distributions in Millimeter Wave 3GPP New Radio Systems

Abstract: The recently standardized millimeter wave-based 3GPP New Radio technology is expected to become an enabler for both enhanced Mobile Broadband (eMBB) and ultra-reliable low latency communication (URLLC) services specified to future 5G systems. One of the first steps in mathematical modeling of such systems is the characterization of the session resource request probability mass function (pmf) as a function of the channel conditions, cell size, application demands, user location and system parameters including m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The height of UEs, NR BS, and blockers are assumed to be constant and given by h U , h A , and h B , We assume the orthogonal frequency division multiple access (OFDMA) scheme as specified in NR [36]. Depending on UE locations, the number of PRBs required to serve multicast UEs might differ and can be computed using NR MCS according to the procedure outlined in, e.g., [37].…”
Section: A Deployment Traffic and Resource Modelsmentioning
confidence: 99%
“…The height of UEs, NR BS, and blockers are assumed to be constant and given by h U , h A , and h B , We assume the orthogonal frequency division multiple access (OFDMA) scheme as specified in NR [36]. Depending on UE locations, the number of PRBs required to serve multicast UEs might differ and can be computed using NR MCS according to the procedure outlined in, e.g., [37].…”
Section: A Deployment Traffic and Resource Modelsmentioning
confidence: 99%
“…While the rates and MCSs are standardized, the corresponding target SINRs are usually vendor-and equipment-specific. We consider the target SINRs in [40], which are shown in Table III (in linear scale) and approximately exhibit increments of twice the previous rate starting from R SBS 1 = 0.2344 bps/Hz. In order to assign R SBS j to the l-th SBS cluster, it is required…”
Section: Rnp-socp-1 Formulationmentioning
confidence: 99%
“…where p B (x ) is available from (17). The authors in [211] demonstrated that the resulting SINR CDF can be well approximated by Normal distribution.…”
Section: A Resource Request Characterizationmentioning
confidence: 99%